The Behavioral Economics of Artificial Intelligence: Lessons from Experiments with Computer Players - Christoph March (Center for Economic Studies and ifo Institute (CESifo), 2019)
Artificial intelligence (AI) is starting to pervade the economic and social life rendering strategic interactions with artificial agents more and more common. At the same time, experimental economic research has increasingly employed computer players to advance our understanding of strategic interaction in general. What can this strand of research teach us about an AI-shaped future? I review 90 experimental studies using computer players. I find that, in a nutshell, humans act more selfishly and more rational in the presence of computer players, and they are often able to exploit these players. Still, many open questions prevail.
Keywords: C90; C92; O33; 330; experiment; robots; computer players; survey